The association of elevated serum lipocalin 2 levels with diabetic peripheral neuropathy in type 2 diabetes - Xi Zhang (Bioscientifica, 2021)
A variety of studies have demonstrated the role of lipocalin 2 (LCN2) in both diabetes and neurological disorders. Nevertheless, the relationship between LCN2 and diabetic peripheral neuropathy (DPN) needs to be elucidated in humans. Therefore, this study aimed to investigate the association of LCN2 with DPN in type 2 diabetes (T2D). A total of 207 participants with T2D and 40 participants with normal glucose tolerance (NGT) were included in this study. All participants were classified in to DPN group and non-DPN (NDPN) group based on the Toronto Clinical Neuropathy Scoring (TCNS). Demographic and biochemical parameters were measured. Serum LCN2 levels wer e determined using an ELISA technique. Serum LCN2 levels in NGT group were lower t han those in either DPN group (P = 0.000) or NDPN group (P = 0.043), while serum LCN2 levels in DPN group were higher than NDPN group (P = 0.001). Moreover, serum LCN2 levels positively correlated to TCNS scores, which reflects neuropathy severity ( r = 0.438, P = 0.000). Multivariate stepwise regression analysis showed that BMI, triglycerides, an d diastolic pressure were independently associated with serum LCN2 in DPN. Additionally, logistic regression analysis demonstrated that LCN2 (odds ratio (OR) = 1.009) and diabetes duration (OR = 1.058) were independently associated with the occurrence of DP N in T2D. Our report reveals the association of serum LCN2 with DPN in T2D. LCN2 mig ht be used to evaluate DPN severity and serve a role in the pathogenesis of DPN.